South Africa Economic Update : Focus on Savings, Investment, and Inclusive Growth - World Bank (Washington, DC, 2017)
The firming of the economic recovery is putting the policy spotlight back on the longer term challenge of faster, more inclusive Gross Domestic Product (GDP) growth. Modest investment rates despite attractive returns and low savings rates despite favorable demographics are important impediments. A virtuous cycle of faster capital accumulation, job creation (especially for the youth), and technological advancement needs to be stimulated. There are no quick fixes that can produce the desired stimulus. The quest for inclusive growth calls for a different, bolder approach. Integration of the advanced and less-developed economies and more effective integration with the global economy, using factory Southern Africa as a platform, hold considerable potential. South Africa's medium-term growth prospects point to a strengthening recovery. GDP growth is projected to be 3.5 percent in 2011, 4.1 percent in 2012 and 4.4 percent in 2013. The long term potential growth rate under the current policy environment is estimated at 3.5 percent. In light of South Africa's low national savings, the reemergence of high current account deficits, financed mostly through volatile portfolio flows, will reemerge as the biggest cause for macroeconomic concern over the medium term. With considerable strengthening of the economic recovery and GDP projected to reach its potential by 2014, the focus shifts back to the longer term challenge of raising GDP growth to 6-7 percent and making it much more inclusive to tackle the extremely high unemployment. This first issue is anchored in the national aspirations of faster and more inclusive growth, with special emphasis on the issues of savings and investment.